1903 Pa. Laws 178, No. 136, §§ 1-2 - (:unkn) unknown (General Publisher, 1903)
Imposed licensing requirement for non-residents and unnaturalized foreign-born resident to possess a gun in the fields, forests, or waters of the State. Punishable by fine.
--
Keywords: REGISTRATION